Seed Germination Mechanism of Carex rigescens Under Variable Temperature Determinded Using Integrated Single-Molecule Long-Read and Illumina Sequence Analysis - Li, Hui; Teng, Ke; Yue, Yuesen; Teng, Wenjun; Zhang, Hui; Wen, Haifeng; Wu, Juying; Fan, Xifeng (Frontiers in Plant Science, 2022)
The turfgrass species Carex rigescens has broad development and utilization prospects in landscaping construction. However, seed dormancy and a low germination rate have inhibited its application. Furthermore, the molecular mechanisms of seed germination in C. rigescens have not been thoroughly studied. Therefore, in the present study, PacBio full-length transcriptome sequencing combined with Illumina sequencing was employed to elucidate the germination mechanism of C. rigescens seeds under variable temperatures. In general, 156,750 full-length non-chimeric sequences, including those for 62,086 high-quality transcripts, were obtained using single-molecule long read sequencing. In total, 40,810 high-quality non-redundant, 1,675 alternative splicing, 28,393 putative coding sequences, and 1,052 long noncoding RNAs were generated. Based on the newly constructed full-length reference transcriptome, 23,147 differentially expressed genes were identified. We screened four hub genes participating in seed germination using weighted gene co-expression network analysis. Combining these results with the physiological observations, the important roles of sucrose and starch metabolic pathways in germination are further discussed. In conclusion, we report the first full-length transcriptome of C. rigescens, and investigated the physiological and transcriptional mechanisms of seed germination under variable temperatures. Our results provide valuable information for future transcriptional analyses and gene function studies of C. rigescens.